(untitled) (Damascus University Journal of agriculture sciences, 2021)
The study was carried out at Abu Jarash Farm, faculty of agriculture, University of Damascus, during the years of 2017-2018 in order to study the effect of sodium nitroprocess treatment (SNP) at concentrations 10 and 20 mg/L in addition to the effect of cold storage on prolonging flower life and maintaining the qualitative characteristics of two varieties of Gerbera (Shamra and Lisa). Research parameters included weight loss, post-harvest life, water absorbed, diameter of flower. The results showed superior treatment with SNP at the concentration of 10 and 20 mg/L, in Shamra and Liza, in reducing weight loss after harvest, The treatment under cold storage conditions was characterized in reducing the weight loss. Lisa with treatment SNP 10 and SNP 20 under cold storage had the lowest proportion of weight loss (0.88 and 1.23%, respectively) compared to non-cold treatment. The weight loss was significantly increased in Shamra cultivar with the non-cold and cooled control flowers (7.02 and 5.23, respectively) compared with the other treatments. The post-harvest life of the control flower (Shamra) under cold storage condition was 12 days compared to 6 days for the non-cold (control) flower. Flowers under cold storage treated with SNP10 and SNP20 continued for up to 18 days in good condition. Cold storage reduced the amount of absorbed water, while the amount increased with SNP treatment, especially the non-cooled 20 mg / L concentration for both the Shamra and Liza varieties (38.17, 29.33 ml / flower, respectively).